THE INFLUENCE OF LIFESTYLE AND SOCIAL MEDIA MARKETING ON CUSTOMER LOYALTY OF BEAUTY STUDIOS IN MANADO - Sauba, Yulitha K.; Mangantar, Maryam; Wangke, Shinta J. C. (Universitas Sam Ratulangi, 2021)
In the current era of development, everything continues to develop, in every development it brings broad changes in accordance with technological advances and ultimately leads to changes in the lifestyle of everyone. The trend of lifestyle and the digital world that is growing rapidly, provides opportunities for business ventures in the beauty industry, one of which is the beauty studio which has been widely spread throughout Indonesia, especially Manado. The beauty industry uses social media as a place to support and promote through pictures, videos, or other information that customers can easily monitor. The increasing number of beauty services is driven by a lifestyle and human nature that is basically never satisfied and various other supporting factor. The purpose of this study was to determine whether the variables of lifestyle and social media marketing affect customer loyalty at the Beauty Studio in Manado. This study uses quantitative methods with data collection using questionnaires and multiple linear regression as a tool to analyze the data that has been collected. The sample size of this study was 100 respondents, especially the millennial generation aged 20-35 years who are users of beauty studios who have done eyelash extensions or nail art in Manado. The results of this study found that social media marketing has a positive and significant effect on customer loyalty, while lifestyle has a positive but not significant effect on customer loyalty.Â Keywords: Lifestyle, Social media marketing, Customer loyalty